Bacterial wilt and drought stresses in banana production and their impact on economic welfare in Uganda: implications for banana research in East African Highlands - Abele, S.; Pillay, M. (Informa UK Limited, 2007)
This study investigates the economic impact of banana Xanthomonas wilt (bxw) and drought on banana production in Uganda. The objective of this research is to determine the benefits of targeted research to avoid economic losses. In the worst-case scenarios, spread of bxw at a rate of 8% per annum, or drought at 50% yield losses in a five-year interval, results in significant losses for both consumers and producers. These losses would not only seriously jeopardize food security, but also affect overall macro-economic performance in Uganda. More likely scenarios with lower bxw and drought losses still show high economic losses, but they are mainly occurring on the consumers' side. Producers benefit from price increases at small production losses. This implies that research has to focus on public goods that can be delivered at no cost to farmers, as farmers under these circumstances are not likely to adopt costly preventive management measures. The best bet in this case would be publicly financed breeding, plant material multiplication and dissemination. Other options may be quarantine or trade restrictions, however, research on linkages between trade and the spread of bxw is yet to be done.